HAZAIRIN'S INTERPRETATION OF INHERITANCE VERSES IN THE QUR’AN AND ITS INFLUENCE ON THE COMPILATION OF ISLAMIC LAW (JOURNAL OF INDONESIAN ISLAM, 2023)
Hazairin is a leading figure in legal reform in Indonesia and is famous as the pioneer of the idea of Indonesian madhhab. This paper examines Hazairin's interpretation of the Qur’an issued to bilateral and mawāly theories in the inheritance system in Indonesia and the implications of his interpretation. This study uses a hermeneutic approach to interpreting the Qur'an, which looks at how Hazairin reads and provides interpretations of inheritance law verses in the context of inheritance in Indonesia. The results showed that Hazairin interprets the inheritance verses differently as he tries to present these verses by considering local values. Hazairin's interpretation of the Qur'an Surah al-Nisa (4): 7 has found the bilateral system, which is adopted in article 174 of the Compilation of Islamic Law (KHI), and his interpretation of the Qur'an Surah al-Nisa (4): 33 has found the new concept of mawāly system and is adopted the Compilation of Islamic Law Article 185. For this reason, this study argues that the interpretation by referring to prevailing local values as carried out by Hazairin can provide a strong foundation, but it should always refer to the source of Islamic law.